A Study of the Effectiveness of the Bigdeli Mind Silumation Method in Football Ball Control Using Functional Magnetic Resonance Imaging - Kamarzarin, Hamid; Bigdeli Shamloo, Mojtaba (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to investigate the effectiveness of the Bigdeli Mind Silumation method in football ball control using functional magnetic resonance imaging (fMRI). Methods and Materials: The present research employed an experimental single-case design with pretest and posttest assessments. The participant was a 35-year-old female student at Payame Noor University, Karaj, in 2022, who was selected through convenience sampling. An fMRI scan was initially obtained before the participant received Bigdeli Mind Silumation training for football ball control. Twenty days after the Bigdeli Mind Silumation intervention, another fMRI scan was conducted, and activity in different brain regions was examined using criteria similar to those applied in the first assessment. Each fMRI session lasted 10 minutes, during which the participant remained at rest. The data were analyzed by Engineer Malekian using FSL software. Findings: The results showed that, following subtraction analysis of the activity identified within the network, motor-network activity and signal intensity increased after the specified training period. Conclusion: Given the study design, this increase may indicate the effects of the training and practice intervention. Increased motor-network activity was diffusely observed in both the right and left hemispheres. This network was associated with the participant’s motor activity of keeping the ball balanced on the foot.